Statistical study of emergency appendectomies performed at the military hospital of Guayaquil-Ecuador - Cabezas Tamayo, César Gastón (Revista Universidad de Guayaquil, 1988)
From August 1982 to August 1987, a total of 158 emergency appendectomies were performed at the Guayaquil Military Hospital. Early diagnosis and early surgery reduce morbidity and mortality in acute appendicitis
Keywords: Appendicitis; appendectomy; emergency; statistics